Case Report: Giant Biatrial Myxoma Mimicking Malignant Cardiac Tumor in a Patient With a Hepatic Angiomatous Mass - Fan, Chengming; Zhang, Hao; Zhuang, Huanwei; Jiang, Zenan; Tan, Haoyu; Iroegbu, Chukwuemeka Daniel; Song, Long; Liu, Liming (Frontiers in Cardiovascular Medicine, 2021)
Cardiac myxomas, primarily originating from the left atrium, are the most prevalent types of benign cardiac tumors; however, biatrial myxomas are extremely rare. Herein, we present a rare case of a 55-year old male with exertional dyspnea and intermittent chest discomfort due to a giant biatrial mass with concomitant atrial fibrillation and hepatic hemangioma. The giant tumor with its peduncle at the interatrial septum involved both atria; however, bulging through the tricuspid valve to the right ventricle during systole. Hence, excision of the giant cardiac tumor (which grossly composed of three parts: stiff, fleshy, and soft) and Cox-Maze IV procedure was performed with the resected specimen measuring 100 × 80 × 40mm. The patient who was in a stable condition was discharged home on the 12th postoperative day. Thus, given the excellent postoperative results achieved, surgical treatment in large multi-cavitary benign cardiac tumors is feasible and should be considered a potentially curative therapy.